JavaScript Bible - Goodman, Danny (Bible, 2010)
The bestselling JavaScript reference, now updated to reflect changes in technology and best practices As the most comprehensive book on the market, the JavaScript Bible is a classic bestseller that keeps you up to date on the latest changes in JavaScript, the leading technology for incorporating interactivity into Web pages. Part tutorial, part reference, this book serves as both a learning tool for building new JavaScript skills as well as a detailed reference for the more experienced JavaScript user. You'll get up-to-date coverage on the latest JavaScript practices that have been implemented since the previous edition, as well as the most updated code listings that reflect new concepts. Plus, you'll learn how to apply the latest JavaScript exception handling and custom object techniques. Coverage includes:  JavaScript's Role in the World Wide Web and Beyond Developing a Scripting Strategy Selecting and Using Your Tools JavaScript Essentials Your First JavaScript Script Browser and Document Objects Scripts and HTML Documents Programming Fundamentals Window and Document Objects Forms and Form Elements Strings, Math, and Dates Scripting Frames and Multiple Windows Images and Dynamic HTML The String Object The Math, Number, and Boolean Objects The Date Object The Array Object JSON - Native JavaScript Object Notation E4X - Native XML Processing Control Structures and Exception Handling JavaScript Operators Function Objects and Custom Objects Global Functions and Statements Document Object Model Essentials Generic HTML Element Objects Window and Frame Objects Location and History Objects Document and Body Objects Link and Anchor Objects Image, Area, Map, and Canvas Objects Event Objects Practical examples of working code round out this new edition and contribute to helping you learn JavaScript quickly yet thoroughly.